A Novel Hybrid Multi Criteria Decision Making Model: Application to Turning Operations - Sofuoglu, Mehmet Alper; Orak, Sezan (International Journal of Intelligent Systems and Applications in Engineering, 2017)
Multi criteria decision making models (MCDM) are extensively used in material and process selection in engineering. In this study, a novel hybrid decision making model is developed. Best-Worst method (BWM) is hybridized with TOPSIS, Grey Relational Analysis (GRA) and Weighted Sum Approach (WSA). Developed hybrid models produce similar results in different weight value of decision makers so they are combined. The model is tested in a turning operation and an optimization study is conducted by using Taguchi experimental design. The developed model can be used by engineers and operators in manufacturing environment.